MODERN TRENDS AND INNOVATIVE METHODS IN TEACHING FOREIGN LANGUAGES - Isayeva, Umida (Educational Research in Universal Sciences, 2023)
“Modern Trends and Innovative Methods in Teaching Foreign Languages” explores contemporary approaches and strategies in language education. The Abstract highlights diverse aspects, including technology integration, communicative competence, task-based learning, cultural integration, personalized learning, gamification, blended learning, project-based learning, neuroeducational insights, assessment innovations, and online language communities. The exploration aims to provide insights into the dynamic landscape of language teaching, emphasizing creativity, engagement, and effective methodologies.